Discourses and decision making : a case study of a relocating town - Laitinen, Maria (fi=Lapin yliopisto|en=University of Lapland|, 2009)
The aim of this thesis is to describe the decision making process and the discourses involved with it in Kiruna. The rationality of these political, social, economical and environmental discourses is studied. The research uses qualitative methods, in particular contents analysis as a research method to analyse the data. The main source data is thus qualitative in character, and involves conference presentations and email correspondence between the author and the interviewer. The most important conclusion is that the discourses are the “arena” for the decision implementation. It can, however, be argued that “discursiveness” of decision making is only seeming, because the decision has already been made, and even though the discourses were constructed already before the decision, its real influence on the decision cannot be proved. Whether the decision is made by consulting the whole community or only a handful of people, the outcome always seems to reflect the circumstances, the present situation and the future expectations of the local people. Discourses are constructed within the social context, and the prevailing ambience. The “togetherness” of the locals makes it easy to believe that the town will survive the upcoming challenges and changes without major social difficulties. The ability to cope and adjust, the resilience of the locals and their acceptance about the development is in this case the corner stone that can save the community. Since the decision in Kiruna was set up by the changing conditions, it can be argued that it was the circumstances that made the decision. The discourses only “cushioned” and justified what was already decided. The discourses are thus constructed in and with the help of the socioeconomic context. Based on the analysis it can be concluded that the sociopolitical circumstances that the decisions are made in are the driving force for the outcome. It should also be noted that the external pressure and influence on the outcome is crucial. In the case of Kiruna, it is possible that ...